Haemato-Biochemical Studies of Acephate Induced Toxicity and its Amelioration by Picrorhiza kurroa in Female Wistar Rats - Londhe, S. A.; Gangane, G. R.; Moregaonkar , S. D.; Ghorpade, P. B. (International Journal of Livestock Research, 2019)
An experimental trial on subacute toxico-pathological studies of Acephate and its amelioration by Picrorhiza kurroa was attempted in thirty female Wistar rats for 28 days through haemato-biochemical assessment. The experimental rats were divided into 5 groups each comprising of 6 rats. The group I and III were kept as a control and plant control, respectively. The rats of group II were Acephate toxicated, the rats of group IV and V were toxicated with Acephate and treated with Picrorhiza kurroa. Significant reduction in Hb, TEC, PCV, TLC values and non-significant differences in DLC were observed. There was significant increase in mean values of AST, ALT, ALP and BUN whereas mean STP, cholesterol, sodium, potassium and Acetylcholinesterase values were significantly decreased in group II and IV. These altered mean values could be due to Picrorhiza kurroa.